دور استراتيجيات المزيج التسويقي لتحقيق الجودة والتميز في الخدمات المصرفية - محريق, فوزي (جامعة الوادي - University of Eloued, 2008)
يعد المزيج التسويقي الركيزة الأساسية والأداة الفعالة في التسويق المصرفي، ولا تكون عملية التسويق ناجحة إلا بتخطيط إستراتيجيات مزيج تسويقي فعال يتماشى ومتطلبات السوق المصرفي؛ وتسعى المصارف جاهدة من خلال ذلك إلى تحقيق الجودة والتميز في خدماتها المصرفية المتنوعة. The marketing mix is the cornerstone and the most effective tool in banking marketing. The marketing process is successful only by planning effective marketing strategies in line with the requirements of the banking market. Banks strive to achieve quality and excellence in their diverse banking services.
مقال
Keywords: التسويق المصرفي، الخدمات المصرفية، الجودة; Marketing Banking, Banking, Quality